Green potential of Europe's labour force: Relative share and possible skills imbalances - Michael Lobsiger; Christian Rutzer (University of Basel, Center of Business and Economics (WWZ), 2021)
Using a data-driven methodology that allows to quantify the importance of different skills in performing green tasks, we estimate the green potential for 26 European countries. By green potential we mean the share of employed persons in occupations characterised by skills that are important for the exercise of green tasks to total employment. For the countries considered, we estimate a green potential between 7.1% and 16.8%, with the manufacturing and energy & construction sectors having above-average and the resources and services sectors below-average shares. We further examine the green potential with regard to a possible shortage of skilled workers by means of indicators that reflect different dimensions of skills shortages. Estimates of skills short ages related to the green potential reveal considerable heterogeneity among the investigated countries. Nevertheless, occupations with a high green potential are generally characterised by a tense skilled labour situation. Looking at four occupational groups, results reveal that the need for skilled workers with high green potential is particularly pronounced for managers and professionals, while being lower for technicians and smallest for craft & related trades workers.
Keywords: J23; J24; Q52; 330; green transition; labor market; skills shortage